A EAD dança? corporalidade do digital - Motta, Everson Luiz Oliveira (2022)
This thesis argues that the construction of knowledge in learning dance agglutinates knowledge regarding the body, which is mature or sufficient to be able to be mediated by digital format, ubiquitous and at a distance. Also, in search of the sense of bodily, political and social experience of dance, there is evidence of the problem of devaluation of their professionals and their bad remuneration at all levels of teaching and learning in dance, and regarding training and accessibility. Dance is seen by various segments of society as a strong sedimentation agent for the devaluation of its art. The political chain of the union is out of step with the necessary actions to enhance a national and cultural good and that it can generate income, help people and contribute to the national cultural growth. From that context born or objective of this work analyze the how to teach dance, in the undergraduate course in Dance at distance learning (EAD) in UFBA, in the educational structure of its curriculum, it is consistent with the purposes of an Onlife education. As a methodology, we sought in Cartography a possibility of producing on top of already existing data and updating other procedures in a continuous process of knowledge and updating. Starting from the junction of rhizomes, in an open and connected map in all its dimensions, disassembled, reversible, susceptible to constant modifications (DELEUZE; GUATTARI, 1995). There is a need to observe the social changes in dance and culture (SANTAELLA, 2013 SANTANA, 2006; WOSNIAK, 2010). We use the concepts of techniques and technologies in the philosophical contributions of Vieira Pinto (2005) in the context of surveillance capitalism (ZUBOFF, 2021) and in the training of teachers (ALMEIDA, 2021 TARDIF, 2014) in order to create unprecedented viable (inédito Viável) (FREIRE, 2013) in new curricular proposals. In addition to a redemption of the activities and two values of contemporary dance, or the meaning of physical dance altered to teach it as a legacy for new generations, for the creation of a true cultural industry that generates income, value and work. The data shows that 50% from students use the Virtual Learning Environment (VLE), which is more efficient for carrying out homework at a distance, in addition to two e-books, which give them support, and the professors-tutors who are relevant do not academic course. Given the use of the Internet, they assert that, despite the difficulties, future dance teachers will be able to access the course, apart from being able to enter the world of work, or that they can open doors to new teachers. The conceptual platforms for the teaching of Arts/Dance in the degree in Dance in the distance dance modality of the Federal University of Bahia (UFBA) enrich the concept of teaching dance with the mixed activities of distance learning activities. I concluded that dance as culture and art, in this space, is Onlife, multidisciplinary and creates new ways to reach the distance places in the state of Bahia. A corporeity that dances in differentiated spaces and with almost infinite difficulties coexists not a movement that makes the art of dance flourish. Builds in student’s theunderstanding of dance in EAD, which has long been lived by the student's body, to be trained as a teacher